Microfilm Preservation in Libraries: A Systematic Literature Review - Awalia Latifa Mayda Ikrimah; Nisrina Amani (Indonesian Journal of Librarianship, 2025)
Background: Microfilms are susceptible to damage over time. The lack of guidelines, materials and reference materials on microfilm is also the reason why the use and maintenance of microfilm in libraries is still rare. Many libraries and librarians are not fully aware and prepared to maintain and care for microfilm so that it can be used for a long time.  Purpose: To review the literature on microfilm preservation so that through this research, the extent of scientific development and knowledge that has been produced by experts is known. Method: A systematic literature review with a qualitative approach was used to collect literature relevant to the topic. The formulation of research questions used the population, intervention, comparison, outcome, and context (PICOC) framework and the search strategy used Boolean logic. Literature sources came from Google Scholar, which was then tested for quality. The analysis technique used content analysis by describing the research findings. Result: The majority of the literature reviewed came from India and Nigeria with the highest number of publications in 2023. Traditional microfilm preservation techniques are carried out by providing a special place and controlling environmental conditions. Meanwhile, digital preservation techniques are carried out by digitizing through data migration. The constraints of microfilm preservation that are often encountered are financial limitations. Conclusion: From the results of the systematic review, it was found that storage in a separate room and digitization are often done in libraries to preserve microfilms with limited funds as the main obstacle.Keywords: Library; Library Material; Microfilm; Preservation